A new location of rare and listed in the "Red Book of the Altai Region" species for the Ust'-Pristan District of the Altai Region - P. A. Kosachev; E. A. Kruchkova; P. D. Gudkova (Acta Biologica Sibirica, 2017)
The article contains a new distribution data of rare plant species listed in the "Red Data Book of the Altai Region" for the territory of the Ust'-Pristan District of the Altai Region. During the study of the flora of this region, five species of rare plants, previously not listed for the area, were found, as well as two species for which new places in the area were discovered. In addition, for each species, information about the new location, distribution in the Altai Region and a common one, as well as a map is given.